DINAMIKA REGULASI EMOSI KARYAWAN YANG MENGALAMI ABUSIVE SUPERVISION - Erza Agistara Azizah; Kadek Fitriyanti; Nadia Shafira Putri; Andi Andyna Maharezky Edhy; Hebby Lutfionin Butsyaina; Ahmad Robeth Felasufia Naoval; Wiwin Hendriani (Jurnal Psikologi, 2023)
This research was conducted based on the phenomenon of abusive supervision faced by employees. Abusive supervision experienced by employees, namely verbally and non-verbally. The purpose of this study is to understand the dynamics of emotional regulation in employees who experience abusive supervision. The subjects of this study were three employees who were selected using a purposive sampling technique. This study used a qualitative method with a phenomenological approach. Data were collected through in-depth interviews on the subject and references to journals, books, research results and other data provided for research. The analysis technique used is Interpretative Phenomenological Analysis (IPA). The findings indicated that the process of regulatory dynamics carried out by the three research subjects included 3 (three) phases, namely the assessment phase, the emotional experience phase, and the behavioral response phase. The individual's tendency to develop and comply with standards despite experiencing abusive supervision can be an indication that the individual has good emotional regulation dynamics, while the individual's tendency to be passive is an indication of obstacles in the dynamics of emotional regulation.